Change in mineral weathering behaviors of a bacterium Chitinophaga jiangningensis JN53 under different nutrition conditions. (31st January 2017) - Cheng, Cheng; Wang, Qi; He, Linyan; Sheng, Xiafang
Abstract : Bacteria play important roles in mineral weathering and soil formation. However, little is known about the nutrition‐related changes in mineral weathering potential and pattern of bacteria. In this study, mineral weathering behaviors of a novel mineral‐weathering bacterium Chitinophaga jiangningensis JN53 were characterized in the presence of three contrasting biotite or potassium feldspar‐added media. C. jiangningensis JN53 increased more Fe release from the minerals in the M‐BHm (nutrition‐poor medium) than in the SSKM (nutrition‐rich medium) and BHm (nutrition‐moderate medium), while C. jiangningensis JN53 released more Al from the minerals and Si from biotite in the SSKM. Similar Si release from potassium feldspar by C. jiangningensis JN53 was observed in the SSKM, BHm, and M‐BHm. K releasing ability of C. jiangningensis JN53 was significantly higher in the biotite‐added M‐BHm. Highest and lowest growth of C. jiangningensis JN53 was observed in the SSKM and M‐BHm, respectively. In the presence of the minerals, C. jiangningensis JN53 mainly produced gluconic acid in the SSKM and acetic acid in the BHm and M‐BHm. C. jiangningensis JN53 also produced large amount of succinic acid in the biotite‐added SSKM and oxalic acid in the potassium feldspar‐added M‐BHm. The results showed the growth, production of organic acids, and mineral weathering ability of C. jiangningensis JN53 in the three contrasting nutrition conditions. The results also suggested the change in the mineral weathering behaviors of C. jiangningensis JN53 under different levels of nutrition conditions.